APPLICATION STRATEGY LEARNING HEURISTICS IN INCREASE RESULTS STUDY MATHEMATICS STUDENT CLASS V ELEMENTARY SCHOOL - Riyantini, Agus; Namotemo, Hendriane; Paruntu, Patrice Ester (STKIP Singkawang, 2023)
The problem of learning mathematics at SD 06 satai c class v shows that learning outcomes are still low, this research aims to 1) To determine the increase in learning outcomes using heuristic learning strategies in class V of SD Negeri 06 Satai C. 2) To see the results of mathematics learning reaching the KKM individually by implementing heuristic learning strategies in class V of SD Negeri 06 Satai C. 3) To find out whether student learning activities are classified as good in debit material when heuristic learning strategies are applied. The research used was a quasi experimental design research with a one group pretest-posttest design. The population of this study was class V students at SD Negeri 06 Satai C. The sample was class V with a total of 24 students. N-Gain test to see improvements in student mathematics learning outcomes. The result is N-Gain = 0,318 with medium criteria in the range 0,3 ≤ N – gain < 0,7. The results show that there is an increase. Next, use the one sample t-test formula. The normality test results showed that was 6,355 and was 7,814. Because ≤ is 6,355 ≤ 7,814, it is normally distributed, so it is known that = 5,915 and = 2,010, we get = 5,915 2,010 then Ha is accepted and Ho is rejected. So it can be concluded that individual students' mathematics learning outcomes reach the KKM. Next, to find out students' learning activities, use an observation sheet. From the data, the percentage of student learning activities is 85%. This shows that students' learning activities during learning are in the very active category and are classified as good.